2018
DOI: 10.1523/jneurosci.2919-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Connectivity Differences Underlying Inhibitory Control Across the Adult Life Span

Abstract: Inhibitory control requires precise regulation of activity and connectivity within multiple brain networks. Previous studies have typically evaluated age-related changes in regional activity or changes in interregional interactions. Instead, we test the hypothesis that activity and connectivity make distinct, complementary contributions to performance across the life span and the maintenance of successful inhibitory control systems. A representative sample of healthy human adults in a large, population-based l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 79 publications
8
70
0
1
Order By: Relevance
“…As the in vivo studies that formed the basis of these predictions for emotional reactivity 5 and inhibitory control 6,7 were fMRI studies conducted in younger adults, further research is needed to investigate how LC connectivity or reactivity is related to age-related changes in LC structural integrity. For example, a recent study using Cam-CAN data showed age-related differences in the relationship between NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15410-w ARTICLE response inhibition performance and brain connectivity but not activity in a distributed inhibition network 49 , which raises the possibility of compensatory changes in response to age-related reductions in LC structural integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the in vivo studies that formed the basis of these predictions for emotional reactivity 5 and inhibitory control 6,7 were fMRI studies conducted in younger adults, further research is needed to investigate how LC connectivity or reactivity is related to age-related changes in LC structural integrity. For example, a recent study using Cam-CAN data showed age-related differences in the relationship between NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15410-w ARTICLE response inhibition performance and brain connectivity but not activity in a distributed inhibition network 49 , which raises the possibility of compensatory changes in response to age-related reductions in LC structural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…For emotional regulation and reactivity, we used the negative regulation score (computed by subtracting the negative emotion rating from the negative watch condition from the negative regulate condition) and the negative reactivity score (computed by subtracting the neutral watch score from the negative watch score), respectively 53 . The stop signal response time (SSRT) measures response inhibition during a Stop-Signal/No-Go task and was used to represent inhibitory control 49 . To measure overall executive function, we used the time taken to complete the Hotel task, which tests the ability to plan and multitask 54,55 .…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant to the research in neurocognitive aging, and may reduce selection bias, for example by permitting the inclusion of individuals with a wider range of hypertension, cardiovascular conditions or comorbidity. The use of RSFA as a mechanism to adjust for confounds in BOLD-fMRI, or as a predictor, will allow the development of better models of ageing and age-related disorders (Cabeza et al, 2018;Tsvetanov et al, 2018). Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing is consistently related to weakened within-network connectivity co-occurring with increased between-network connectivity (Geerligs 2015, Betzel 2014. Crucially, the coordination of within-and between-network connectivity supports the maintenance of general cognition (Tsvetanov et al, 2016) and performance in specific cognitive domains Tsvetanov et al, 2018) across the lifespan.…”
Section: Introductionmentioning
confidence: 87%